Marco conceitual para estudar a relação entre materiais curriculares e professores de Matemática - Januario, Gilberto (2017)
In this research we aimed to construct the conceptual framework that can guide the analysis of the teacher-curriculum materials of Mathematics. We developed an investigation from the perspective of theoretical research oriented by the question: What conceptual framework can guide the study concerning the relationship between curriculum materials and teachers of Mathematics? The thesis is organized in a multi-paper format, consisting of an introductory chapter, three articles and a chapter of considerations. The theoretical reference is about the discussion regarding the relationship between curriculum materials and teachers in the Mathematics Education’s area; the theories about the concepts of affordance and agency; and papers about scientific research on mathematical curriculum materials. As a result, it stands out the non-neutrality in the relation between teachers and curriculum materials by these two agents of curriculum development, evidencing the knowledge, beliefs and values of Mathematics, its teaching and the students formative course. The concepts of affordance and agency are emphasized as a framework that guides the study and understanding of the different uses of curriculum materials, as well as the displacement of the agency, sometimes in the materials (with their affordances and restrictions), or in the teachers (with their knowledge, beliefs and values); and it is evidenced the investment on changes of paradigm in the research on Mathematics curriculum materials: from descriptive questions regarding the characteristics of the materials to those that investigate correlation and causality between different phenomena related to these curriculum resources. The teacher- curriculum materials relationship requires discussion and research that takes different curriculum materials, teacher praxis and the teacher-curriculum relation as research objects for the production of knowledge. The observation of affordance and agency, as a conceptual framework discussed by us, reveals different concepts related to the interaction between teachers and curriculum materials, which demand research proposals to understand the ways in which these notions influence the interaction and potentiate the curriculum development: knowledge, beliefs and values; curriculum fidelity; curriculum insubordination; institutional context; planning set; teachers as curriculum producers; and decolonization of the curriculum